Zeitschrift für celtische Philologie (De Gruyter, 1897)
Zeitschrift für celtische Philologie (ZcP) was founded in 1897 by Kuno Meyer and Ludwig Christian Stern. It is thus the oldest significant journal of Celtic studies still in existence. In the early period, its focus was on Celtic (mainly Irish) philology and 'linguistic monuments' to Continental Celtic (mainly Gaulish) languages. Later, these areas were extended to include new Celtic languages and typological questions.